Регулювання витрати рідини у гідравлічній системі введенням у потік додатків - Орел, Вадим (Видавництво Національного університету «Львівська політехніка», 2002)
In clause the possibility of regulation of the flow rate in pipework by change of hydraulic resistances by enter into a flow the hydrodynamic active additives is shown.